The effect of omission on the consistency of the text in a book - Naeem Amouri - Mahmoud Abdanan Mehdi Zadeh - Jumaa Hamidi Hassouni ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Mentioning all the details in the hadith requires a large area of effort and time, for both the writer and the recipient, in addition to the prevalence of boredom. That is why human languages have relied on a kind of brevity, which is the omission of some elements. It is unreasonable for people to write everything. They say it or understand it in complete sentences, because the Arabic language shares with all the languages of the world its tendency to ease and abbreviate. Therefore, in our research, we will address the effect of deletion on the consistency of the text, in the book “Revealing the secrets” by al-Maqdisi, and what it achieved in terms of brevity and intensification of the significance of the meaning.